PROBLEMATIKA PERWAKAFAN DI INDONESIA (Telaah Historis Sosiologis) - Arifin, Jaenal (ZISWAF, 2014)
Understanding of the Indonesian people against the waqf understanding thatit is not separated by a factor of history. In the history of the Islamic Waqfendowment trajectory has been known and done long ago mankind before Islamcame. This gives rise to a different understanding of the waqf. To anticipatethe negative impact of the Indonesian public’s understanding of the waqf thenpresumably necessary alternative solutions assess, analyze and then formulatemanagement strategies and implement them in order to develop sustainableendowments.